High Prevalence of Anti-HCV Antibodies Among Pregnant Women in Southwestern Nigeria (2017)
Hepatitis C virus (HCV) is the most common cause of cirrhosis, hepatocellular carcinoma and liver transplantation. While universal screening for other blood-borne viruses (BBVs) such as HIV and HBV among pregnant women is recommended in Nigeria, no such recommendation exist for HCV in the country. Despite recently developed direct-acting antiviral agents (DAAs) to cure HCV at high rates and at very high cost, the absence of an HCV vaccine or approved therapy during pregnancy makes prevention of vertical transmission impossible at the moment. Using a commercially available enzyme linked immunoassay technique, prevalence of antibodies to hepatitis C virus (anti-HCV) was determined among pregnant women attending antenatal clinics in Southwestern Nigeria. Of the 273 serum samples obtained from the pregnant women 9.5% was positive for anti-HCV antibody. There were differences in anti-HCV prevalence by age and locality. Results of the study confirm endemicity of HCV among pregnant women in the country, consequently, we advocate free screening, among other essential measures for HCV intervention in Nigeria.